An Efficient Certified Email Protocol - Shao, Jun; Feng, Min; Zhu, Bin Benjamin; Cao, Zhenfu (Information Security Conference, 2007)
A certified email protocol, also known as a non-repudiation protocol, allows a message to be exchanged for an acknowledgement of reception in a fair manner: a sender Alice sends a message to a receiver Bob if and only if Alice receives a receipt from Bob. In this paper, we present a novel approach to combine the authorized Diffie-Hellman key agreement protocol with a modified Schnorr signature effectively to construct our certified email protocol. Our proposed certified email protocol is an optimistic protocol, with an off-line trusted third party being involved only when a party cheats or the communication channel is interrupted during exchange. We also compare our protocol with other optimistic certified email protocols, and conclude that our certified email protocol is the most efficient optimistic certified email protocol.